Nutritional and biological value of bakery products with the addition of vegetable powders and milk whey - Kassymov1, Samat; Amirzhan, Togzhan; Moldabayeva, Zhanar; Rebezov, Maksim; Sharova, Tamara; Gribkova, Vera; Gaidarenko, Larisa; Karapetyan, Irina (International Journal of Psychosocial Rehabilitation, 2020)
Bakery products are part of the daily diet of people and can be considered as a perspective basis for the design of functional food products. To enrich bakery products, Narine milk whey, egg-shell powder and IR-dried beet and cranberry powders were used as functional additives. A total of 6 samples with different combinations of additives were tested. It was shown that introduction of "Narine" whey, beet and cranberry powders, egg-shell powder not only improves organoleptic characteristics of products, but also gives them functional properties in terms of protein and calcium content in comparison with traditional technology. Thus, the addition of 3% egg shells increases the calcium content to 52.5 mg/100g. The method of mathematical modelling by the decision of problems of linear programming shows optimality of the chosen formulas.